You are on page 1of 52

# 19

2 Lagrange

2.1

(x) stationary

(2.1.1)

x n {x1 , , xn }

x1
.
n
.
x
. Rcol
xn

(2.1.2)

x : Rn R x
m x {1 (x) , , m (x)}

1 (x)

..
: Rn Rm
(x) =
.

m (x)

(2.1.3)

(1 , , m ) : Rm R

(2.1.4)

(x) (1 , , m ) (x)

## (x) = (1 (x) , , m (x)) stationary

(2.1.5)

3
(x) stationary

= 0

j = 0

j
j=1

(2.1.6)

x f (x) x
f : Rn R
[
f
f x

f
xn

Rnrow

(2.1.7)

2 Lagrange

20

f f

x 3
{x1 , , xn }
n

x1
.
n
.
x
. Rcol
xn

(2.1.8)

w =

j = 0

j
j=1

(2.1.9)

x f

f f x

(2.1.10)

x (2.1.6) (2.1.9)

(2.1.9)
w = 1 1 + + m m = 0

(2.1.11)

(2.1.11) (2.1.9)

w = f

(2.1.12)

x f (x) f

= 0

(2.1.13)

2.2 w
w = f
f 2.4

g1 (x)

g (x)
r

= g1
..
.

(2.1.14)

= gr

{g1 , , gr } x gk r
{x1 , , xn }

(x) (2.1.5)

2.1.

21

{x1 , , xn }
x
xi {g1 , , gr }
(2.1.14)
Lagrange

w (x)

g1 (x) = g1

..
s.t.
.

g (x) = g
r
r
=

(2.1.15)

(x, ) = w (x) +

## k (gk (x) gk ) stationary

(2.1.16)

k=1

(2.1.16)
r
x,

x1
[
]
.
.. Rncol , 1 r Rrrow ,
x

xn

[
f

f
x1

f
xn

f
Rnrow ,

f
1

..
.

Rrcol .

(2.1.17)

(2.1.18)

f
r

f
x
(2.1.16) x
f

(2.1.19)

= 0 =
j +
k gk = 0
x
j
j=1
m

(2.1.20)

k=1

x x
w =

r
m

j +
k gk = 0
j
j=1

(2.1.21)

k=1

(2.1.21) (2.1.11)
(2.1.21)

(2.1.16)

g1 (x) g1

=0

g (x) g
r
r

=0
..
.
=0

(2.1.22)

2 Lagrange

22

(2.1.16) x
x (2.1.21)

g1 = = gr = 0

(2.1.23)

w =

j = 0

j
j=1

(2.1.24)

x
x (2.1.15)

Lagrange ??
Lagrange J. L. Lagrange
[Lagrange,

## Boissonnade & Vagliente (1997)] 1788

Lagrange
2.2

Lagrange

2.3

2.4 2.2

2.2
2.2

2.2

[Schek (1974)]

2.2.

2.2.1

23

[Schek (1974)]

(x) =
wj L2j (x) stationary,

(2.2.1)

wj Lj j
x
x,y z x, y, z n
{x1 , , xn } n x x
x
Lj
2.2.5
(2.2.1) (2.2.1)

(2.2.1)

= 0

2wj Lj Lj = 0

(2.2.2)

n x (2.2.2)

w =

2wj Lj Lj = 0

(2.2.3)

w = f x f (x) : Rn 7 R

w =

(2.2.4)

= 0

(2.2.5)

L j

qx

L j
qy

L j

qz

nj

nj
Lj
p

nj

1
L j

px

Lj

L j
p y

L j

pz

(a) Lj

(b)

2.1:

2 Lagrange

24

(2.2.1)

= 0

(2.2.6)

2wj Lj Lj = 0

(2.2.7)

(2wj Lj Lj x) = 0

(2.2.8)

2wj Lj Lj x = 0,

(2.2.9)

x x

2wj Lj Lj = 0

(2.2.10)

(2.2.1)

{x1 xn } x,y,z

Lj
Lj (xp , yp , zp , zq , yq , zq )

## (xp xq )2 + (yp yq )2 + (zp zq )2 ,

(2.2.11)

p, q j {xp , , zq }

{xp , , zq } {x1 , , xn } Lj
{xp, yp , zp } {xq , yq , zq }
2.5
{xp, yp , zp } {xq , yq , zq } Lj
2.1(a) Lj Lj

2.1(b) nj
nj

2.1(a) (b) m

nj Lj = 0.

(2.2.12)

j=1

nj Lj Lj nj

2.2.

25

nj = nj (Lj )

nj Lj = p.
(2.2.13)
j=1

(2.2.12) x

w =

nj Lj = 0,

(2.2.14)

j=1

Lj Lj (2.1.10)

(2.2.12) m nj

n = [n1 , , nm ]

(2.2.15)

(2.2.12) , nj

qj = 2wj

(2.2.16)

qj
(2.2.10) nj qj Lj
m

qj Lj Lj = 0.

(2.2.17)

j=1

wj qj
x (2.2.17)

w =

qj Lj Lj = 0

(2.2.18)

j=1

## (2.2.14) (2.2.3) (2.2.18) (2.2.1) x

n = [2w1 L1 , , 2wm Lm ]

(2.2.19)

n = [q1 L1 , , qm Lm ]

(2.2.20)

2 Lagrange

26

(2.2.1)
(2.2.19) (2.2.20)

wj =

nj
nj
, qj =
2Lj
Lj

(2.2.21)

## (2.2.3) (2.2.18) 2wj Lj qj Lj Lj

( ) 1
( )
w = wj L2j = qj L2j
2

(2.2.22)

( )
12 qj wj L2j

(2.2.10) (2.2.17) n
n n

(2.2.1) Lj (2.2.11)
Lj
j
L

j
L

Lj
xp

Lj
yp

Lj
zp

Lj
xq

Lj
yq

Lj
zq

]
(2.2.23)

Lj x
2.5
[
j = xp xq
L
Lj (x)

yp yq
Lj (x)

zp zq
Lj (x)

xq xp
Lj (x)

yq yp
Lj (x)

n
L
q = n /L
(a)

(b)

2.2:

zq zp
Lj (x)

]
.

(2.2.24)

2.2.

27

j Lj (x)
L

Lj Lj
j
qj Lj L
[
= qj px qx py qy pz qz

qj
0
0
qj
0

0
q
0
0
q
j
j

0
0
qj
0
0

=
qj
0
0
qj
0

0
q
0
0
q
j
j

0
0
qj
0
0

qx px

qj

qj

qy py

px

py

pz

,
qx

qy

qz

j=1 qj Lj Lj

qz pz

(2.2.25)

= 0

D x = D f xf ,
D y = D f y f ,

(2.2.26)

D z = D f z f ,
D x,y z
f
D x,y z [Schek

(1974)] px , py , pz
D x = D f xf + px ,
D y = D f y f + py ,

(2.2.27)

D z = D f z f + pz ,
[Schek (1974)]

Force Density, FD qj

qj = nj /Lj .

(2.2.28)

(2.2.21) qj 2.2(a) nj Lj

j
nj Lj
[Schek (1974)]

(2.2.26) (2.2.27)
D

2 Lagrange

28

D D 1

x = D 1 (D f xf + px ) ,
(
)
y = D 1 D f y f + py ,
z = D

(2.2.29)

(D f z f + pz ) ,

(2.2.26) (2.2.27)

(2.2.24)

D Lj

xT D x =

xT D f xf + xT px

y T D y

y T D f y f + y T py

z T D z

z T D f z f + z T pz

(2.2.30)

(2.2.3) (2.2.18)
D Lj

(2.2.1)

2.4

## THEOREM 1. Each equilibrium state of an unloaded network structure with force

densities qj is identical with the net, whose sum of squared way lengths weighted by
qj is minimal.

2.2.

2.2.2

29

## [Maurin & Motro (1998)] B. Maurin

R. M. O. Pauletti [Pauletti (2008)]

Cauchy

(2.2.31)

2 2

=
t

(2.2.32)

t
(2.2.28) j
Qj

Qj = j /Sj ,

(2.2.33)

Sj j j j

Qj

Sj (x) j Sj x, y, z
x
x, y, z

x1
.
.
x=
. ,
xn
R
2

S P

Q
Q
2 q

(2.2.34)

2 q
R
(a) S

p P
2

(b)

2.3:

2 Lagrange

30
Sj

S
S
, ,
x1
xn

]
(2.2.35)

x, y, z

Sj 2.3(a) Sj
t

Cauchy
=

=
t

2.3 (b)
2.3(a) (b) m

j Sj = 0,

(2.2.36)

j=1

(2.2.36) x

w =

j Sj = 0.

(2.2.37)

j=1

(2.2.33)
(2.2.36)
m

Qj Sj Sj = 0

(2.2.38)

j=1

w =

Qj Sj Sj = 0.

(2.2.39)

j=1

w =

(x) =

1
j=1

wj =

Qj Sj2 (x)

1
Qj
2

(2.2.40)

(2.2.41)

(x) =

(2.2.42)

j=1

(2.2.42) wj

w =

j=1

2wj Sj Sj = 0,

(2.2.43)

2.2.

2wj Sj Sj = 0.

31

(2.2.44)

j=1

wj Qj
(2.2.36)(2.2.37)

wj =

1 j
2 Sj

(2.2.45)

(x) =

(2.2.46)

## wj Sj2 (x) stationary,

(2.2.47)

j=1

(x) =

j=1

w =

w =

j=1
m

2wj Lj Lj = 0,

(2.2.48)

2wj Sj Sj = 0,

(2.2.49)

j=1

2wj Lj 2wj Sj Lj Sj

w =

w =

j=1
m

( )
wj L2j = 0,

(2.2.50)

( )
wj Sj2 = 0,

(2.2.51)

j=1

2.2.3

B.2

2 Lagrange

32

(x) =

## Sj2 (x) stationary.

(2.2.52)

j=1

(x) =

Sj (x) min

(2.2.53)

j=1

B.2

2.4 3 2.5

R=10.0

2.4:

(a-1)

(b-1)

S h:4.0 area:121.7

(a-2)

S h:6.5 area:185.4

(b-2)

2.5:

S 2 h:4.0 area:121.7

S 2 h:6.5 area:185.4

S 2

2Sa
2Sb

2.6:

2.2.

33

(2.2.52)
2.5(a-1)(b-1) (a-2)(b-2)

j Sj2 j Sj

w =

w =

j=1
m

Sj = 0,

(2.2.54)

2Sj Sj = 0.

(2.2.55)

j=1

(2.2.55) Sj Sj

2.6 (2.2.54)
Sj Sj
1
2.5

j Sj2

2.2.4

(x) =

j=1

wj L2j (x) +

## wj Sj2 (x) stationary,

(2.2.56)

j=1

2.7 (2.2.56)

2.7:

2 Lagrange

34

2wj Lj Lj +

j=1

2wj Sj Sj = 0.

(2.2.57)

j=1

w =

2wj Lj Lj +

j=1

2wj Sj Sj = 0.

(2.2.58)

j=1

(2.2.56) (2.2.57)

wj

Lagrange

(x, ) =

Sj (x) +

j=1

(
)
k stationary
k Lk (x) L

(2.2.59)

k=1

[ (2008)]
Sj j Lk k Lk
k
L
k
[
]
= 1 r

(2.2.60)

= 0

Sj +

j=1

k Lk = 0

(2.2.61)

k=1

w =

Sj +

L1 (x)

L (x)
r

k Lk = 0.

(2.2.62)

1
=L
..
.

(2.2.63)

r
=L

r (2.2.59)
}
{
1, , L
r Sj
L
j

(2.2.58) (2.2.62)

2.2.

w =

j Sj +

35

nk Lk = 0.

(2.2.64)

(2.2.65)

(2.2.58)

j , nk (2.2.62)

j = 1, nk = k

(2.2.66)

k
k x

2.2.5

## [Vassart & Motro (1999); Zhang & Ohsaki (2006)]

2.8:

2 Lagrange

36

2.9
X -X -

(2.2.26)

D x = 0, D y = 0, D z = 0,

(2.2.67)

0 x,y,z D

x = y = z = D 1 0 = 0

(2.2.68)

x = 0, y = 0, z = 0,

(2.2.69)

(2.2.67)

trivial solution
(0, 0, 0)

D
D D 1 (2.2.68)

## D (2.2.67) complementary solutions)

D null space / kernel)

D =0

(2.2.70)

q1

q5
q2

q1

q3

q6
2
4

q4
(a)

q3

q5

q6

q2

q4

4
(b)

2.9: X -

2.2.

37

2.9 X - D

D = C T QC,

1 0

1 0

0 1

C=
0 1

1 1

0 0

q1 0

0 q2

0 0

Q=
0 0

0 0

0 0

(2.2.71)

0 1

1 0

,
0 1

0
0

1 1
0

0
q3

0
0

0
0

0
0
0

q4
0
0

0
q5
0

(2.2.72)

,
0

q6
0
0

(2.2.73)

C Q [Schek (1974)]
){q1 , , q4 } {q5 , q6 }
D

D=

q1 q2 q5
q5
q1
q2

q5
q3 q4 q5
q3
q4

q1
q3
q1 q3 q6
q6

q2
q4

.
q6
q2 q4 q6

(2.2.74)

D (2.2.67)

{q1 , , q6 } 1:1:1:1:-1:-1 D
D

1 1 1
1

1 1 1
1
,
D=
1
1 1 1

1
1 1 1

1
1
0

1
1
0

x = a + b
+ c 1 ,
1
0

1
0
1

1
1
0

1
1
0

y = d
+ e 0 + f 1 ,
1

1
0
1

1
1
0

1
1
0

z = g + h
+ i 1 ,
1
0

1
0
1

(2.2.75)

(2.2.76)

(2.2.77)

2 Lagrange

38

## {a, , i} 2.9(a) (b)

(2.2.67)
{a, d, g}
{q1 , , q6 } 1:1:1:1:-1:-1 X -

(a, d, g)
x = y = z = 0
(2.2.77) D

{q1 , , q6 } 1:1:1:1:-1:-1

2:2:2:2:-1:-1 D

3 1 2
2

1 3 2
2

,
D=
(2.2.78)
2 3 1
2

2
2 1 3

1
1

1
1

x = a , y = b
, z = c

1
1

1
1

(2.2.79)

1
1
1

{a, b, c}
(a, b, c)

(x) =

## wj L2j (x) stationary,

(2.2.80)

j=1

w1

w1
L5

w2

w3

L6

w4
(a)

w3

L5

w2 L6

w4

4
(b)

2.10: X -

2.2.

39

X - (2.2.80)

(2.2.80)

{x1 , , xn }

wj L2j
X - (2.2.80)

X -

Lagrange Lagrange
(2.2.80)

(x, ) =

wj L2j (x) +

j=1

(
)
4+k stationary,
k L4+k (x) L

(2.2.81)

k=1

k j k Lagrange
wj k L
k

= [1 , 2 ]

(2.2.82)

2.10 wj
{
}
k {w1 , , w4 } L
5, , L
6
L

(2.2.81)
{
}
5, L
6 1:1
{w1 , , w4 } 1:1:1:1 L
2.10(a) (b) (2.2.81) c2 = a2 + b2
2.10(a) (b)

(x, ) =

j=1

wj L4j (x) +

(
)
4+k ,
k L4+k (x) L

(2.2.83)

k=1

Lj
(2.2.83) 3
{w1 , , w4 } 1:1:1:1
{
}
5, L
6 1:1 2.10(a)
L

1:8:8:1 2.10(b)

2 Lagrange

40

(2.2.83) x
=

4wj L3j Lj +

j=1

k L4+k = 0.

(2.2.84)

k=1

w =

4wj L3j Lj

j=1

k L4+k = 0.

(2.2.85)

k=1

(2.2.83)

L (x)
5
L (x)

5
=L

(2.2.86)

6
=L

(2.2.83)

nj Lj = 0

(2.2.87)

j=1

w =

nj Lj = 0

(2.2.88)

j=1

w =

nj (Lj )Lj +

j=1

k L4+k = 0.

(2.2.89)

k=1

(2.2.83)
[
n = [n1 , , n6 ] = 4w1 L31 ,

, 4w4 L34 , 1 ,

]
2

(2.2.90)

(2.2.87)

nj = 4wj L3j

(2.2.91)

wj nj

wj =

nj
4L3j

(2.2.92)

(2.2.85)

2.2.

41

(2.2.83)

(x, ) =

1
2

(
)
j 2
kj Lj (x) L

k ) stationary,
k (Lk (x) L

(2.2.93)

(x, ) =

wj L4j (x)

k ) stationary,
k (Lk (x) L

(2.2.94)

(2.2.83)
[Kazuma & Noguchi (2006)]

j j
(2.2.93) kj L

k k
L
2.11(a) (2.2.93) (2.2.94)
(2.2.94) 2.11(b)

(2.2.94) (2.2.93)

(2.2.94)
(2.2.93) (2.2.94)

w =

w =

(
)
j Lj +
k Lk = 0,
kj Lj L

4wj L3j Lj +

(2.2.95)

k Lk = 0,

(2.2.96)

(
)
j
(2.2.95) Lj kj Lj L
(
)
j
Lj L

(a) (2.2.93)

(b) (2.2.94)

2.11:

2 Lagrange

42

(
)
j Lj L
j
L

)
(
j
j = 0 Lj L
L

j = 0
L

(2.2.94) (2.2.96)
j = 0
L

(2.2.94)

w =

( )
wj L4j +
k Lk = 0,

(2.2.97)

wj = nj /4L3j L4j

2.2.6

(x, ) =

wj L4j (x) +

wj Sj2 (x) +

(
)
k
k Lk (x) L

(2.2.98)

k x
L

(a)

4wk L3j Lj +

(b) 1

2wj Sj Sj +

k Lk = 0

(2.2.99)

(c) 2

(d) 3

2.12:

2.2.

43

w =

4wk L3j Lj +

2wj Sj Sj +

k Lk = 0

(2.2.100)

w =

nj Lj +

j Sj +

k Lk = 0

(2.2.101)

3
2.12

2.2.7

2.1
2.2 2.3
2.1:

(a)

[Schek (1974)]

[ Bletzinger (2001)]

wL2 stationary.

(b)

S stationary.

## [Maurin & Motro (1998)]

(c)

(e)

(g)

wS stationary.
2

(d)

=
wL2 + wS 2 stationary.

1
2 + (L L)

=
k(L L)

=
wL4 + (L L)

stationary.

(f)

stationary.

[ (2008)]

## [Miki & Kawaguchi (2010)]

=
S + (L L)
stationary.

{ 2}

=
wL4 +
wS + (L L)
stationary.

(h)

2 Lagrange

44

2.2:

(a)

[Schek (1974)]

[ Bletzinger (2001)]

2wLL = 0

w =

S = 0

(b)

w =

(c)

(e)

(g)

w =
2wSS = 0

w =
2wLL + 2wSS = 0

(d)

w =
k(L L)L
+ L = 0

w =
4wL3 L + L = 0

(f)

[ (2008)]

## [Miki & Kawaguchi (2010)]

w =
S + L = 0

w =
4wL3 L + {2wSS} + L = 0

(h)

2.3: x

(a)

[Schek (1974)]

[ Bletzinger (2001)]

=
2wLL = 0

=
S = 0

(b)

(c)

2wSS = 0

(d)

2wLL + 2wSS = 0

(e)

(g)

2.2.8

=
k(L L)L
+ L = 0

=
4wL3 L + L = 0

(f)

[ (2008)]

## [Miki & Kawaguchi (2010)]

=
S + L = 0

=
4wL3 L + {2wSS} + L = 0

(h)

2.2.

45

(x, ) =

j (Lj ) +

j=1

j (Sj ) +

j=1

k (gk gk ),

(2.2.102)

k=1

gk gk

j
j

= 0 =
Lj +
Sj +
k gk = 0,
x
Lj
Sj
j=1
j=1
m

(2.2.103)

k=1

g1 (x) = g1

..
=0
.
.

gr (x) = gr

(2.2.104)

x x
w =

m
M
r

j
j
Lj +
Sj +
k gj = 0.
Lj
Sj
j=1
j=1

(2.2.105)

k=1

w =

nj Lj +

j=1

j Sj +

j=1

Rk gk = 0

(2.2.106)

k=1

(2.2.105)

nj =

j
j
, j =
, Rk = k
Lj
Sj

(2.2.107)

= 0

(2.2.108)

(2.2.106) (2.2.102)
}
{
1
m
{n1 , , nm , R1 , , Rr } =
, ,
, 1 , , r ,
(2.2.109)
L1
Lm
{
}
1
M
{1 , , M } =
, ,
,
(2.2.110)
S1
SM

## k (gk (x) gk ) stationary.

(2.2.111)

k=1

w gk gk
2.1

2 Lagrange

46

]
w
w
=
, ,
, = [1 , , r ]
1
m

(2.2.112)

g1
1
.
.

= .. , J = ..
gm
m

(2.2.113)

Jw

2.1

= J w + J = 0.

(2.2.114)

w = J w ,

(2.2.115)

= w + J = 0.

(2.2.116)

w = ( J w + J ) x = 0,

(2.2.117)

w = (w + J ) x = 0.

(2.2.118)

e = J w x, g = J x

(2.2.119)

w = e + g = 0

(2.2.120)

w = w x

(2.2.121)

w = w + g = 0

(2.2.122)

2.3

Lagrange

2.3. Lagrange

2.3.1

47

J. Bernoulli J. Bernoulli

## Principle of lever 2.13

pP + qQ = 0.

(2.3.1)

P
q
p
A

B
2.13:

2 Lagrange

48

p, q P, Q
(2.3.1)
(2.3.1) p, q P, Q
(2.3.1)
2.13 P Q
{P, Q}

P
Q

[
=

(2.3.2)

A, B (2.3.2) (2.3.1)

pA qB = 0,

(2.3.3)

(pA qB) = 0.

(2.3.4)

## (2.3.4) (pA qB)

pA qB = 0,

(2.3.5)

pA = qB,

(2.3.6)

(2.3.1)

2.3.2

(Composition of forces)
Newton

2.14

f F + g G + h H = 0,

(2.3.7)

f , g, h F , G, H

F = G = H

(2.3.8)

2.3. Lagrange

49

f r + g r + h r = 0,

(2.3.9)

(f + g + h) r = 0,

(2.3.10)

f + g + h = 0,

(2.3.11)

r
(2.3.9) f , g, h r

2.3.3

2.15
2.15

f
g
r

h
2.14:

2 Lagrange

50

( F ) f )
2.15(a)

4F = f

H, h

F H + f h = 0,

(2.3.12)

F, f H, h
f

h H (2.3.12)
F f H h
2.15 {H, h}
[
] [
]
H
4
=
h
h
1

H
h

[
=

1
41

(2.3.13)

]
H

(2.3.14)

(2.3.12)

4F h + f h = 0,

(2.3.15)

(4F + f ) h = 0,

(2.3.16)

f = 4F

(2.3.17)

F
h

f
f

(a)
2.15:

(b)

2.4.

51

1
F H f H = 0,
4)
(
1
F f H = 0,
4

(2.3.18)
(2.3.19)

f = 4F

(2.3.20)

2.15(a)
2.15

## (2.3.17) (4F + f ) h (2.3.20)

(
)
F 41 f H

2.4

2.2 Lj Sj Vj
Vj {Lj , Sj , Vj }
2.16{Lj , Sj , Vj } {x1 , , xn }
2.5
{Lj , Sj , Vj }
( )
( )
N
T N
T
j
j

2.2

Lj

Sj

Vj

Lj

2.16:

Sj

Vj

2 Lagrange

52

( )
N
T [ (1995) ]
j

2.4.1

Einstein N M

N
1
N
N
dv det gij d d , v
dvN
(2.4.1)
M

N N = 1, 2, 3
2.17 {l, a, v}

v 1 = l, v 2 = a, v 3 = v

(2.4.2)

## dv1 = dl, dv2 = da, dv3 = dv

(2.4.3)

(
)
1 , , N M
M1 , , Mn
(
)
1 , , N
n

vN =
dvN
(2.4.4)
j=1

Mi

(2.4.4) gij
{
}
1 , , N

g = det gij ,

g = det gij

(2.4.5)

dv N =

det gij d1 dN

(2.4.6)

(2.4.1)
[ (1977); (2001)]

N= 1

N = 2

2.17: N

N =3

2.4.

v N =
gd1 dN (1 i, j N ) .

53

(2.4.7)

v N N = 1, 2, 3
{l, a, v}

v 1 = l, v 2 = a, v 3 = v

(2.4.8)

g = g ij gij g
(2.4.9)
2
A.1.5 g ij gij
gij gij
gij

1
v N =
g ij gij dvN (1 i, j N )
2 M

1
g ij gij dvN = 0 (1 i, j N ) .
v N =
2 M

1
i g kj gij dvN = 0 (1 i, j, k N )
v N =
2 M k

(2.4.10)

(2.4.11)

(2.4.12)

i
k

wN =

1
2

i kj
Tk
g gij dvN = 0 (1 i, j, k N )

(2.4.13)

i
Tk

(2.4.13) N M
i
i
(2.4.13) Tk
Cauchy k

i
i
i
i
i
i
(N = 3) ,
= k
(N = 1) , Tk
tk
(N = 2) , and Tk
Ak
Tk

(2.4.14)

A, t M

21 gij

eij

eij di dj =

1
(gij gij ) di dj ,
2

eij =

1
gij ,
2

(2.4.15)

(2.4.16)

2 Lagrange

54

gij gij
(
)
1 , , N gij
(2.4.16) eij gij

Green-Lagrange Euler-Almansi
B.5 Green-Lagrange

1
i g
j
(gij gij ) g
2
Euler-Almansi
E=

e=

(2.4.17)

1
(gij gij ) g i g j
2

(2.4.18)

i g i
g
(gij gij )

eij =

1
2

1
(gij gij )
2

(2.4.19)

(
)
gij eij 1 , , N gij
eij N N
i
Tk

i kj
T ij = Tk
g

wN =

1
2

(2.4.20)

T ij gij dvN = 0 (1 i, j N )

(2.4.21)

i
T ij Tk

## [ (1995); Bletzinger et al. (2005)]

2nd Piola-Kircho (2.4.21)

gij

d
v=

gd1 d2 d3

(2.4.22)

g
J=
g

(2.4.23)

g = det gij

i kj
2nd Piola-Kircho Cauchy ij = k
g

i g
j .
S = J ij g

(2.4.24)

2.4.

55

i g
j Green-Lagrange
g

E=

1
i g
j .
(gij gij ) g
2

(2.4.25)

1
i g
j

gij g
2

(2.4.26)

E =

S : Ed
v=

i kj
k
g gij dv

(2.4.27)

w3 (2.4.27)
2nd Piola-Kircho
Green-Lagrange

2.4.2

Galerkin

1
=
2

i kj
Tk
g gij dvN = 0,

(2.4.28)

gij
3

(2.4.28) gij

n {x1 , , xn } x, x, f =
f
x

x1
x1
[
.
.

x=
.. , x = .. , f =
xn
xn

f
x1

f
xn

]
(2.4.29)

(2.4.28)

n n gij (2.4.28)
n gij (2.4.28) x
n gij gij

gij = gij x,

(2.4.30)

{
}
gij 1 , , N {x1 , , xn }
(
)
(2.4.30) gij {x1 , , xn } gij 1 , , N
(
)
gij 1 , , N , x1 , , xn gij n
Galerkin
gij
n {x1 , , xn }

2 Lagrange

56

gij

gij
gij

1
=
2

i kj
Tk
g
gij dvN = 0,

(
)
1
i kj

Tk
g gij dvN x = 0.
2 M

(2.4.31)

(2.4.32)

x x

(x) =

1
2

i kj
Tk
g gij dvN = 0.

(2.4.33)

(2.4.30)

1
(x) =
T i g kj gij dvN p = 0.
2 M k

(2.4.34)

p n

n
i
i
Tk
= k

(
)
i
i
(x) = l N = 1, Tk
= k
)
(
i
i
= k
(x) = a N = 2, Tk
)
(
i
i
= k
(x) = v N = 3, Tk

(2.4.35)
(2.4.36)
(2.4.37)

l, a, v
(x) = f

f (x) : Rn 7 R (x) = 0
(x) = 0 (x) = 0 = 0
3

2.4.3

(x) = 0 3

(x) N

( ) 1
N
T g g dvN ,
T

2 j

(2.4.38)

2.4.

57

(
)
dvN 1 , , N

1

T
g g dvN =
N
j ,
2 M

(2.4.39)

(x)

(x) =

( )
N
T ,
j

(2.4.40)

( )
T p,
N
j

(2.4.41)

(x) =

( )
N
T (2.4.38)
j
N

2.18 1,2,3 N
N + 1

{
}
p1 , , pN +1
(
)
1 , , N

0 1 N

(
)
(
)
r 1 , , N = 1 (p1 p2 ) + + N pN pN +1 + pN +1
(2.4.42)
{
}
p1 , , pN +1

(
)
1 , , N

gi

r
,
i

(2.4.43)

(0,0,0) g
4

(1,0)

(0,0)

(0,0,1)

g2

g2

Sj
(1)

Lj
g1
(a) N=1

(0)

(1,1)

Vj
2

(0,1)

(1,1,1)

g1
(b) N=2
2.18: N

g1
(c) N=3

(0,1,1)

2 Lagrange

58

{g 1 g N }

g i = pi pi+1 (1 i N ) ,

(2.4.44)

gij = g i g j

(2.4.45)

i
i
Tk
gij Tk

N = 1, 2, 3

( ) 1 [ 1 11
]
1j T
Lj T1 g g11 j ,
2
( ) 1 [
]
2j T
Sj T g g j (, , = 1, 2) ,
2
(
)
]
1 [

3j T
Vj T
g g j (, , = 1, 2, 3) ,
2
Lj , Sj , Vj

Lj = det g11 ,

(2.4.46)
(2.4.47)
(2.4.48)

(2.4.49)

Sj =

1

det g (, = 1, 2) ,
2
j

(2.4.50)

Vj =

1

det g (, = 1, 2, 3) .
6
j

(2.4.51)

1
det g (, = 1, , N )
N!

(2.4.52)

VjN =

g 2.5.3 g ij gij
N = 1, 2, 3 2.6 (x)

(a) j1(Tik=ik)

(b) j2(Tik=ik)

(c) j3(Tik=ik)

( ) (
)

2.19: N
T T =
j

2.4.

2.4.4

59

( )
N
T {Lj , Sj , Vj }
j

2.19
(2.4.46) (2.4.48) T

( ) (
)

1j T
T =
= Lj ,
( ) (
)

2j T
T =
= Sj ,
(
)
(
)

T
=
= Vj .
3j T

(2.4.53)
(2.4.54)
(2.4.55)

(2.4.12)
( )
N
T {Lj , Sj , Vj }
j
( )
i

N
T Tk
j
N
j = f

f (x) : Rn 7 R {Lj , Sj , Vj }
f (x) N
j
(x)

gij T
T
= T
(gij )

Lj Sj 2.5
1j 2j
g ij gij Lj Sj
Vj
( )
T
{Lj , Sj , Vj } N
j

2.4.5

(x) =

j = 0
j

j=1

( )
N
T p = 0
j

(2.4.56)

(2.4.57)

j=1

T

p = 0

(x) = 0 3
(x)

2 Lagrange

60

gij p

2.4.6

gij T
T
= T
(gij )

(gij )
= T
T

N M

N

g g dvN = 0
w =
T

(2.4.58)

[
w

W , ,

]
d d
1

(2.4.59)

(
)
E=
W 1 , , N d1 dN

(2.4.60)

E = 0

(2.4.61)

T = T
g

g
J=
g

(2.4.62)

(2.4.63)

2nd Piola-Kircho

S = JT ,

(2.4.64)

2.4.

61

2.4.1

1
(g g ) ,
2

e =

(2.4.65)

(
)
g 1 , , N

S = C e

(2.4.66)

C
)
(
g 1 , , N

g d
v

T g dvN = wN

(2.4.67)

d
vN

d
vN =

gd1 dN

(2.4.68)

W =

1
C
e e g
2

]
W d d
1

d
vN =

=
M

W
e d1 dN
e

gd1 dN 12 g = e

1
=
S g d
vN
2 M

(2.4.69)

(2.4.70)

(2.4.71)

wN C

S = C e

(2.4.72)

W Galerkin

]
[
1
N
=0

W d d

(2.4.73)

T =

1
C
e
J

(2.4.74)

T = C e

(2.4.75)

W
(2.4.73)

2 Lagrange

62

## (2.4.74) (2.4.75) (2.4.73) 3

(2.4.75)

(2.4.72)

S = 2
g g e +
g g e .

(2.4.76)

gij gij

C =
g g +
g g +
g g

(2.4.77)

(2.4.72) e (2.4.77)
(2.4.76) (2.4.76) s.t.Venant
G
E

E
E
, =
2 (1 + )
(1 + ) (1 2)

E
(
)
1

T
=E
g e +
eij g ij
(1 + )
(1 + ) (1 2)

(2.4.78)

(2.4.79)

gij T
T
(gij )

(2.4.76)

T = 2g g e + e g g

[
]
wN =
2g g e + e g g g dvN = 0

(2.4.80)

(2.4.81)

[
w

]
W d d
1

= E =

[W ] d1 dN

(2.4.82)

B.4

[
]
2g g e g
gij
[
]
e g g g
gij

(2.4.83)

(2.4.84)

(i, j) (, ) (2.4.82) g ij

gij
dA 1
d
A(x)1 = A1
A
dx
dx

(2.4.85)

2.5.

63

)
g
g
1 ( i j
= g
g =
g g + g j g i
gij
gij
2
)
e
1( i j
j i
=
+

gij
4

g
1
g
1
= g
g = g ij g
gij
2
gij
2

(2.4.86)
(2.4.87)
(2.4.88)

[1 (
2

[2g g e
gij

g]

)
)
(
g i g j + g j g i g e + 12 g g i g j + g j g i e
(
)
]
+ 41 g i g j + g j g i + 21 g g e g ij
g

(2.4.89)

(i, j) (, )
(2.4.80)
(2.4.73) 4 (2.4.80)

2.5

Lj Sj g |j
{x1 , , xn } {x1 , , xn } x, y, z
Lj Sj g |j

1
1 + x 1 + x,
(2.5.1)
2
x
1
1
1
1
(1 + x) 2 = 1 + x x2 + x3 .
2
8
16

2.5.1

(2.5.2)

p ,q

xp
xq

p yp and q yq

zp

(2.5.3)

zq

{x1 , , xn }
p q L L
L (xp , yp , zp , xq , yq , zq )

## (xp xq )2 + (yp yq )2 + (zp zq )2 .

(2.5.4)
(2.5.5)

2 Lagrange

64

L
[
]
L L L L L L

L
,
,
,
,
,
.
xp yp zp xq yq zq

(2.5.6)

L
[
]
xp xq yp yq zp zq xq xp yq yp zq zp

L =
,
,
,
,
,
.
L
L
L
L
L
L

(2.5.7)

dp, dq
L

dxp
dxq

dp = dyp , dq = dyq .
dzp
dzq

(2.5.8)

L dL

L
l

dL =
dxp + +
dzq = L
xp
zq
L j

qx

L j
qy

L j

qz

dp
dq

nj

nj
Lj
p

Lj

nj

1
L j

px

L j
p y

L j

pz

(b)

(a) Lj

2.20: L

p
p

L+L

2.21:

]
.

(2.5.9)

2.5.

65

dL L dL

## 2(dxp dxq )(xp xq )

=L 1+
+
L2

dL

(
)
(dpx dqx )(px qx )
L 1+
+

L2
zq zp
xp xq
= L+
dxp + +
dzq
L
l
xp xq
zq zp
=
dxp + +
dzq .
L
L

[

dL = L

dp

(2.5.10)
(2.5.11)
(2.5.12)

]
(2.5.13)

dq

L
p,q
L
2.20
L
L
[
]
p

L L
(2.5.14)
q
2.21 p q p q

2.5.2

p,q,r

xp
xq
xr

p yp , q yq , r yr ,
zp
zq
zr
R
2

S P

Q
Q
2 q

(2.5.15)

2 q
R
(a) S

p P
2

(b)

j
2.22: S

2 Lagrange

66

{x1 , , xn }
p, q,r

1
N N,
2
(N (q p) (r p)) .

S(xp , , zr )

(2.5.16)
(2.5.17)

n=

N
|N |

(2.5.18)

|| |N | = 2S

n=

N
, N N = 4s2
2s

(2.5.19)

S
xp ,

S
, z
r

1

= 1 n
S
(r q) 0 ,

1

, (p r) 0 ,

, (q p) 0 ,

]
,

0
1

0
0

1 , 0 .

0
1

0

1 ,
0

0

1 ,

(2.5.20)

(2.5.21)

S dS
1
(N + dN ) (N + dN )
S + dS =
2

N N + 2N dN ,
2
n
q

r-q
S

2.23:

(2.5.22)
(2.5.23)

2.5.

67

N N = 4S 2

N dN
2S 2
N dN
S(1 +
),
4S 2
N dN
dS =
,
4S
=S

n =

N
2S

1+

(2.5.24)
(2.5.25)
(2.5.26)

dS

dS =

1
n dN .
2

(2.5.27)

dS dN

## N + dN = ((q + dq) (p + dp)) ((r + dr) (p + dp))

= N + (dq dp) (r p) + (q p) (r dp)
dN = (dq dp) (r p) + (q p) (dr dp) ,

(2.5.28)

dp p + p dp = 0

dN = (r q) dp + (p r) dq + (q p) dr

1
0
0

= (r q) 0 dxp + (r q) 1 dyp + (r q) 0 dzp
0
0
1

1
0
0

## + (p r) 0 dxq + (p r) 1 dyq + (p r) 0 dzq

0
1

0
0

1
0

(2.5.29)

+ (q p) 0 dxr + (q p) 1 dyr + (q p) 0 dzr .
0
0
1
dN dS

1
n ((r q) dp + (p r) dq + (q p) dr)
2

1
0
1

= n (r q) 0 dxp + + (q p) 0 dzr .
2
0
1

dS =

(2.5.30)

dxp

dyp

dS = S
dzp
.
.
.
dzr

(2.5.31)

2 Lagrange

68

S
2.22
S
S S S

S =

1
n ((r q) p + (p r) q + (q p) r) .
2

(2.5.32)

p p (r q)p n S
( 2.23 ) p p (r q) p
S p S p
S p, q,r

2.5.3

gij gij

gij
[
gij
ij = gij gij gij
g
Z1
Y1
Z1
XN +1

gij
YN +1

gij
ZN +1

]
(2.5.33)

{Xi , Yi , Zi } (1 i N + 1) i

{x1 , , xn }
(2.4.43),(2.4.44)
(
) (
) (
) (
)
dgij = d pi+1 pi pj+1 pj + pi+1 pi d pj+1 pj , (1 i, j N ) .

(2.5.34)

dgij =
dXi+1 (Xj+1 Xj ) dXi (Xj+1 Xj ) + dXj+1 (Xi+1 Xi ) dXj (Xi+1 Xi )
+ dYi+1 (Yj+1 Yj ) dYi (Yj+1 Yj ) + dYj+1 (Yi+1 Yi ) dYj (Yi+1 Yi )
+ dZi+1 (Zj+1 Zj ) dZi (Zj+1 Zj ) + dZj+1 (Zi+1 Zi ) dZj (Zi+1 Zi ) ,

ij
dgij = g

dx1
dy1
dz1
..
.
dyN +1
dzN +1

(2.5.35)

(2.5.36)

ij
g

2.6

1 1 3 3 gij

2.7.

69

(g11 )
[

g11

g21
g31

g12
g22
g32

g11
g21

g12
g22

]1

1
=
det gij

1
,
g11
[

g22
g21

(2.6.1)
g12
g11

]
,

g13
g13
g12
1

g23 =
g22 g23
det gij
g33
g33
g32

g13
g11
g11
g12

g23 g21 g21 g22 ,
g33
g31
g31
g32

b1
a2 b3 b2 a3
a1

a2 b2 a3 b1 b3 a1 .

a3

b3

(2.6.2)

(2.6.3)

(2.6.4)

(2.6.5)

a1 b2 b1 a2

1,2,3

2.7

Lagrange

Lagrange
Lagrange

70

2 Lagrange